2020
DOI: 10.1002/bies.202000091
|View full text |Cite
|
Sign up to set email alerts
|

Might SARS‐CoV‐2 Have Arisen via Serial Passage through an Animal Host or Cell Culture?

Abstract: Despite claims from prominent scientists that SARS-CoV-2 indubitably emerged naturally, the etiology of this novel coronavirus remains a pressing and open question: Without knowing the true nature of a disease, it is impossible for clinicians to appropriately shape their care, for policy-makers to correctly gauge the nature and extent of the threat, and for the public to appropriately modify their behavior. Unless the intermediate host necessary for completing a natural zoonotic jump is identified, the dual-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…However, in the absence of evidence regarding the last animal intermediate before human contamination (the "proximal" origin of the virus), some authors suggested that SARS-CoV-2 may have been manufactured in a laboratory (synthetic origin) (Segreto and Deigin 2020; Relman 2020). Others suggested that SARS-CoV-2 may result from a chiropteran virus that became adapted to other species in laboratory animal models and then escaped from the laboratory (Sirotkin and Sirotkin 2020). It might also be envisaged that it comes from a viral strain cultured on human cells in a laboratory in order to study its infectious potential, and that has been progressively "humanized" (adapted to humans) by selection of the viruses having the highest ability to spread in these conditions.…”
Section: Of Bats and Men… Plus Some Pangolins?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of evidence regarding the last animal intermediate before human contamination (the "proximal" origin of the virus), some authors suggested that SARS-CoV-2 may have been manufactured in a laboratory (synthetic origin) (Segreto and Deigin 2020; Relman 2020). Others suggested that SARS-CoV-2 may result from a chiropteran virus that became adapted to other species in laboratory animal models and then escaped from the laboratory (Sirotkin and Sirotkin 2020). It might also be envisaged that it comes from a viral strain cultured on human cells in a laboratory in order to study its infectious potential, and that has been progressively "humanized" (adapted to humans) by selection of the viruses having the highest ability to spread in these conditions.…”
Section: Of Bats and Men… Plus Some Pangolins?mentioning
confidence: 99%
“…These investigations indicate as expected that it is possible to adapt bat viruses to infect human cells or various animal models, and that chiropteran CoVs have the potential for direct zoonotic transmission to humans, particularly if they acquire an adapted proteolysis site, which requires only a few mutations or the insertion of a short sequence rich in basic amino acids (Hu et al 2017). This hypothesis has been put forward by Sirotkin and Sirotkin, who developed the hypothesis that the virus might have arisen from serial passages, and accidental escape from the laboratory (Sirotkin and Sirotkin 2020).…”
Section: Genetic Manipulations Of Viruses and Gain-of-function Experimentioning
confidence: 99%
“…This reasoning is however flawed, because it restricts the choice to a dichotomy whereas several other hypotheses are conceivable. In particular, the authors do not consider the possibility that the virus would result from laboratory selection through successive passages between animal species or cells, as discussed in detail by Sirotkin and Sirotkin (Sirotkin et Sirotkin 2020) . Moreover, even though it is not obvious to identify a posteriori any tracer of genetic manipulation and as discussed above, there are currently several traceless options for genetic engineering.…”
Section: /26mentioning
confidence: 99%
“…Most such essays suggest that it instead accidentally escaped from the WIV, after either being manipulated in the laboratory, or perhaps because it was already archived there, reaching the wider population after infecting a researcher. The laboratory escape argument is also considered plausible by the U.S. government which, in addition, has suspended its funding of the EcoHealth Alliance [18] which has reportedly undertaken "gain of function" viral research in China [19].…”
Section: An Alternative Hypothesis For Covid-19: Laboratory Escapementioning
confidence: 99%